Large Shareholders and the Monitoring of Managers: The Case of Antitakeover Charter Amendments - Agrawal, Anup; Mandelker, Gershon N. (Journal of Financial and Quantitative Analysis, 1990)
Anup Agrawal, Gershon N. Mandelker, Large Shareholders and the Monitoring of Managers: The Case of Antitakeover Charter Amendments, The Journal of Financial and Quantitative Analysis, Vol. 25, No. 2 (Jun., 1990), pp. 143-161